Portraits and caftans of the Ottoman sultans - Atasoy, Nurhan 1934-; Kinay, Irem (Assouline, 2012)
From the founding of the Ottoman dynasty by Osman Gazi to Süleyman the Magnificent's legendary territorial conquests, the legacy of the 36 Ottoman sultans has undeniably left its mark throughout the course of history. Featuring exquisite portraits and lavishly decorated caftans, this large-format volume beautifully presents imagery that speaks to the magnificence of the Ottoman Empire and its powerful sultans.